Variants of fixing the knee joint menisci in aged and senile people - Voloshina, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article contains results of a study of 50 knee joints of amputated extremities in people of different sexes at the age of 26-90 without any diseases of the locomotor system. As a result of the above research, the main places and possible variants for fixing the knee joint menisci were studied in people at a mature, elderly and senile age.